Evidências petrográfica, geoquímica e geocronológica do magmatismo alcalino do arco magmático de Goiás na região de Cocalinho, na porção leste do estado de MT - Almada, Jennifer Cardoso Farias (2015)
Post-collisional stages of the Brasiliano/Pan-African Cycle in the region of Cocalinho on eastern Mato Grosso, bordering the State of Goiás, are represented by granitic intrusive bodies associated with mafic and ultramafic rocks. The Itacaiu Pluto is an NE-SWelongated body conform to the regional trend. It is characterized by a expressive magmatism of alkaline nature and composition ranging from monzo the alkali-feldspargranites. This extensive body is defined by three petrographic facies termed biotitegranite Facies, riebeckite-biotite-granite Facies and biotite-granite porphyry Facies. The granitoids show evidence of deformational processes resulting two-phase of deformation, represented mainly by development of penetrative foliation marked by the preferred orientation of minerals placoid, with direction NE and dip to SE, ranging from low to high angle, and mylonitic foliation resultant by strike-slip shear. The chemical composition allowed to classify the rocks as granite type-A, generated in magmatic arc environment and intra-plate post-collisional. Geochronological data U / Pb extracted in zircon crystals indicated crystallization age ranging from 806.6 ± 4.0 to 582.9 ± 6.3 Ma, consistent with those recorded for the Goiás Magmatic Arc. model ages TDM= 0.97 to 1.8 Ga, show positive values of εNd(T) = +4.39, +4.31,+3.69. Positive values of εNd suggest impoverishment of the magma that gave rise to the granitoids in LREE. The negative value of εNd indicates origin from partial melting of continental crust Paleoproterozoic. The rocks mafic-ultramafic occur aligned approximately east-west, with varying degrees of alteration. Define a tholeiitic to calcium-alkaline magmatism, metaluminous, of character intermediate to ultrabasic. The Isotopic studies suggest juvenile character of the parental, magma due to positive values εNd(T). The model ages ranging from TDM = 0.71 to 1,44 Ga and are related to other units of juvenile rocks of the Goiás Magmatic Arc.